Dynamic object replica placement using underlying routing protocols: ensuring the reliability - Waqas, Ahmad; Majeed, Nahdia; Muhammed Yusof, Zulkefli; Wahees Mahesar, Abdul (2013)
Object replication is an unavoidable phenomenon in distributed systems to address the issues of size, administrative and resources scalability. It also guarantees the availability of system as more users can be accommodated and failures can be tolerated. If the location of object replica is not proper, the problem may arise when it is requested by many entities at once. The response time may also increase due to the network latency although network is considered to be steadfast in the distributed systems but the latency can never be avoided. Efficient replica placement, both client initiated and server initiated, can be ensured using the dynamic replica placement mechanism in conjunction with the underlying routing protocols that provides the reliability of contents distribution and minimizes the network latency. In this paper, it is discussed that reliability can be assured if we use replica placement algorithm along with the EIGRP (Enhanced Interior Gateway Routing Protocol). The issues of choosing the best path for placing the replica that provides the minimum latency and reliability of contents transmission can be overcome by combining the EIGRP features that includes internetwork delay, bandwidth consumption, reliability of packet transmission and traffic load, with dynamic replica placement algorithm.